Pelanggaran Maksim dan Strategi Pelanggaran yang Terjadi pada Dialog Aplikasi Chatbot Simsimi Bahasa Arab dan Inggris - Ismi Wafda Maulidiyah; Zaqiatul Mardiah; Dikri Dirwatul Ghozali (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2020)
In the era of technology that continues to develop, the way to communicate also develops. One of them is the chatbot as a friend of human communication. This research examines a chatbot that can make users laugh or upset because of the uniqueness of its responses. That is SimSimi, an artificial intelligence. This research examines the extent of SimSimi can communicate effectively and efficiently. In answering this matter, this research analyzes in what topics the flouting maxims are mostly committed by SimSimi. The analysis process relies on the principle of cooperation Grice (1975). Further, each flouting maxims is explored about the strategy of violations that occur, by referring to the idea of ??Cutting (2002) about the maxim violation strategy. In addition, with SimSimi's multilingual expertise, this research also compares the differences in the frequency of flouting maxims by SimSimi in Arabic and English. Therefore, this research utilizes comparative studies using qualitative methods. The conversations analyzed were 40 conversations containing 4 topics. Based on 20 Arabic conversations, there were 32 flouting maxims. As for the 20 conversations in English, there were 30 flouting maxims. This shows the comparison of the frequency of flouting maxims in Arabic and English dialogue at 16:15. As for the strategies of flouting maxims that occurred, there are 10 kinds of strategies in Arabic dialogue and 6 kinds of strategies in English dialogue. In Arabic dialogues, the topic that contains the most violations of the maxims is the topic of religion. So it is with English dialogue. The results of the research show that SimSimi in English can communicate more effectively and efficiently compared to its use in Arabic.